Good Corporate Governance Enhancing Employee Performance - I Putu Agus Adnyana; Mertyani Sari Dewi (International Journal of Social Science and Business, 2020)
The lack of good governance in government institutions is characterized by inefficient organization and bureaucracy, poor quality of services to the public, difficulty eradicating Corruption, Collusion and Nepotism and lack of community participation in development. This study aims to examines the effect of Good Corporate Governance on the performance of employees of the Agriculture and Animal Husbandry Office of Buleleng Regency. Good Corporate Govenance is measured in terms of fairness, transparency, accountability and responsibility. This study uses a quantitative approach. The population in this study were all employees of the Agriculture and Animal Husbandry Office of Buleleng Regency, both permanent, outsourced and contract employees who totaled 64 people. The number of samples used was 64 employees because the sampling technique used the saturated sample technique. Data was collected using a questionnaire, of the 64 questionnaires distributed, 64 questionnaires were returned with a response rate of 100%. To test the hypothesis, a regression analysis was carried out using SPSS version 17.00 for Windows. Before testing the hypothesis, testing the validity, reliability and classic regression assumptions is tested. This study shows that Good Corporate Governance (fairness, transparency, accountability and responsibility) has a positive influence on employee performance.